ALUR ADMINISTRASI MEDICAL CHECK UP (MCU) RS AWAL BROS BOTANIA - Mulyana, Mulyana; Situmorang, Masriani; Safitri, Risda (Transpublika Publisher, 2024)
Hospitals act as health institutions that are tasked with providing various health services such as outpatient, inpatient, emergency, and referral services which include medical records and medical support used for research, education, and training of health workers. The existence of medical records in hospitals is expected to improve the quality of health services provided, starting from recording data when the patient arrives until the treatment process in the hospital. Furthermore, the management of medical record files is carried out from the processing stage to storage. Hospital administration includes various activities such as planning, supervision, organization, direction, coordination, and evaluation in the provision of hospital health services for the welfare of the community. The main benefit of hospital administration is to ensure optimal health service delivery, by organizing and planning related activities.